Evaluation of the Antiseptic Effect of the Anolyte Solution on Laboratory Rats - S. N. Styazhkina; N. A. Kiryanov; D. N. Kuklin; Kh. S. Kutbedinov; O. N. Eykina; D. V. Strashnov (Антибиотики и Химиотерапия)
An experimental study of the antiseptic properties of the Anolyte solution was carried out. The developed anolyte solution has an antiseptic effect, especially active against Escherichia coli, which indicates the possibility of its use in the complex therapy of purulent wounds.